Evaluating the energy poverty alleviation effect in industrial transition scenarios: Evidence from China - Jun Zhao; Yalin Lei; Sasa Song; Hongyun Huang; Xinwei Qu (Sustainable Futures)
This paper employs China’s 30 provinces as research objects to capture the potential role of industrial transition on addressing energy poverty from two dimensions: industrial supererogation and rationalization. We also explore the heterogeneity and mechanism between the variables. The findings are as follows: (i) Industrial supererogation can effectively address the issue of energy poverty, while industrial rationalization has not played an active role in promoting energy poverty alleviation; (ii) the impact of industrial transition on energy resources poverty shows significant heterogeneity; and (iii) rapid industrial supererogation affects energy resources poverty by improving energy efficiency and adjusting the energy use structure.